Publicly verifiable multi‐secret sharing scheme from bilinear pairings. Issue 3 (1st September 2013) - Wu, Tsu‐Yang; Tseng, Yuh‐Min
Abstract : In a verifiable multi‐secret sharing (VMSS) scheme, multiple secrets are shared among participants during one sharing process in such a way that some qualified subsets of them can recover these secrets. Verifiable property means that one participant may verify his/her own share, but cannot check the validity of the other participants' shares. Verifiable property is deficient for some specific applications such as electronic voting and revocable electronic cash. Publicly verifiable property is more applicable than verifiable property because the shares can be verified by any party. In this study, an efficient publicly verifiable multi‐secret sharing (PVMSS) scheme using bilinear pairings is proposed. Under the computational Diffie–Hellman and modified bilinear Diffie–Hellman assumptions, the authors demonstrate that the proposed scheme is a secure PVMSS scheme.